Cardiovascular Risk Factors in Young Adolescents: Results from the National Health and Nutrition Examination Survey 1988–2016. Issue 5 (May 2021) - Hecht, Eric M.; Williams, Ana-Ysabel P.; Abrams, Gary A.; Passman, Rod S.
Abstract: Objectives: Lifestyle behaviors relevant to cardiovascular health are learned during childhood and continued into adulthood. Children and adolescents who participate in unhealthy behaviors have a higher lifetime risk of cardiovascular disease in adulthood. Public health institutions publish behavior and clinical recommendations designed for adolescents to reduce their lifetime cardiovascular risk. We assessed the prevalence and trends of cardiovascular-relevant behaviors and clinical tests among early adolescents using a nationally representative database. Methods: In 2020, we compared the prevalence of cardiovascular risk factors among 1408 adolescents surveyed from 1988 to 1994 with that of 1812 adolescents surveyed from 2011 to 2016 by obtaining and comparing measures on physical activity, diet, body mass index, smoking status, cholesterol levels, hemoglobin A1c, sodium intake, and blood pressure. Results: The prevalence of adherence to the current recommendations regarding physical activity, diet, and body weight declined over time. Conversely, the prevalence of adhering to recommendations to avoid smoking increased. Clinical indicators, including blood pressure control and normal measures of hemoglobin A1c and total serum cholesterol, showed mixed results, with more individuals showing signs of hyperglycemia, fewer showing signs of hypercholesterolemia, and the percentage of individuals with abnormal blood pressure remaining the same. The use of cardiometabolic medications also increased during the study period. Finally, the number of adolescents with all seven cardiovascular protective factors declined significantly during the study period, from 27.6% to 9.6%. Conclusions: Modern American teenagers aged 12 to 16 years have more cardiovascular risk factors relating mostly to diet, exercise, and obesity than those of a prior generation; however, smoking rates have also declined precipitously. Abstract : Young adolescents who participate less in healthy behaviors have a higher lifetime risk of cardiovascular disease in adulthood. Public health institutions publish behavior and clinical recommendations designed for adolescents to reduce their lifetime cardiovascular risk. The authors assessed the prevalence and trends of cardiovascular relevant behaviors and clinical tests among early adolescents using a nationally representative database.